Correlation of Paedagogical Competence and Professional Competence with Teacher Teaching Performance at SMP Putra Pertiwi, Tangerang Selatan. Banten, Indonesia - Ayuna, Novianty Elizabeth; Gintings , Abdorrakhman (Advances in Social Sciences Research Journal, 2023)
The purpose of this study is to reveal how high the relationship between Paedagogical Competence and Professional Competence and Teaching Performance is owned and carried out by the teacher. The research was conducted at Putra Pertiwi Middle School, a private school located in South Tangerang City, Banten Province, Indonesia. This study uses a descriptive quantitative approach with survey techniques. The data is analysed using the Pearson Product Moment multiple correlation model. As respondents were all 51 teachers, teaching of various subjects in grades 7, 8 and 9. The results of the descriptive analysis showed that Paedagogical Competence was in the high category Professional Competence was in the medium category and Teaching Performance in the high category. The results of the partial correlation analysis prove that there is a significant and strong correlation between Paedagogical Competence and Professional Competence. Pedagogical Competence and Professional Competence are feasible to be estimated as determinants of teaching performance. The weakness of this study is conducted in only one private school and only focuses on two of the four core competencies determined by law, so that it does not represent the various characteristics of schools in all regions of Indonesia. However, it is recommended that both competencies be included as core teacher competencies in the new National Education System Law that is currently being prepared.